Successful Implementation and Development of a Phase II Cardiac Rehabilitation Program: A China-Wide Cross-Sectional Study Tracking In-service Training Clinical Staff - Xun Gong; Xun Gong; Wenliang Zhang; Wenliang Zhang; Jeffrey W. Ripley-Gonzalez; Yuan Liu; Yaoshan Dun; Yaoshan Dun; Yaoshan Dun; Fan Zheng; Ling Qiu; Suixin Liu; et al. (Frontiers Media S.A., 2021)
Background: Despite the benefits of cardiac rehabilitation (CR), phase II CR remains highly unavailable; the factors influential to the successful implementation and development of phase II CR programs have not been fully explored.Methods: A cross-sectional survey was completed by 168 nationwide clinical staff. Parameters associated with the successful implementation and development of phase II CR and the factors associated with the quality of CR were explored by multivariable logistic regression.Results: One hundred and eighteen of 168 respondents' institutions had successfully developed phase II CR programs, 41 of which delivered high-quality CR. Independent factors associated with successful implementation and development of CR were leadership support from hospital administrators, support from resident physicians, staff perception in CR increasing medical risk, and department type (cardiology vs. rehabilitation department). Independent factors associated with CR quality were the availability of "professional CR providers" and staff perceptions of CR improving physician-patient relationships. The medical system factors did not affect the development and quality of CR, including hospital level, funding type, academic type, general/specialized hospital, located city, medical insurance, the existence of a CR outpatient clinic and independent space, the availability of professional CR providers, staff structure, and the availability of regular training and standard procedure.Conclusions: The development and quality of a phase II CR program may benefit from factors including support from administrators and resident physicians, adequately training more CR providers, without viewing medical system factors as a major issue.